Analisis Efektifitas Sistem Pengelolaan Dana Hibah Pada Bagian Kesejahteraan Rakyat Sekretariat Daerah Kabupaten Sukabumi - Agus Suryadi (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to analyze the effectiveness of the grant fund management system at the Social Welfare Division of the Regional Secretariat of Sukabumi Regency. The research employed a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving key informants, including the Head of the Social Welfare Division, grant management officials, administrative staff, internal auditors, and grant recipients. Data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings indicate that the grant management system has generally been implemented effectively and in accordance with applicable regulations. The accuracy of grant recipient targeting was categorized as effective with an achievement rate of approximately 80%, while timeliness of fund disbursement and accountability were categorized as moderately effective with achievement rates of around 70% and 75%, respectively. However, administrative efficiency remains constrained by limited human resources, lengthy bureaucratic procedures, and the absence of an integrated digital grant management system. Furthermore, monitoring and evaluation activities are still focused primarily on administrative compliance rather than outcome measurement. Therefore, the development of an integrated e-Grant system, enhancement of staff competencies, and strengthening of outcome-based monitoring and evaluation are necessary to improve the effectiveness of grant fund management in the future.